Um ambiente virtual para o desenvolvimento de projetos de aprendizagem - Ferrari, Marlon (2014)
This paper aims to present a technological solution to support the development of learning projects (LPs). For this purpose, we attempted to specify and model mechanisms and tools able to cover every step of the LPs development process, in order to promote the collaborative construction and socialization of content.